EXPLORING STUDENT MATHEMATICAL ENGAGEMENT USING ADAPTED WATSON’ ANALYTICAL TOOL - Baiq Rika Ayu Febrilia; Ita Chairun Nissa (LPMPP Universitas Negeri Yogyakarta, 2019)
This research was conducted with the aim of describing the engagement of junior high school students in the mathematics learning process measured using an adapted Watson analytical tool. This research is a qualitative study that analyzes video transcripts of a junior high school teacher in West Nusa Tenggara, East Indonesia who are carrying out mathematical teaching on probability. In this study, the teacher carried out mathematics teaching designed by researchers using the ELPSA (Experience, Language, Pictorial, Symbolic, and Application) framework. The learning process was recorded through a video and then transcribed so that it is easily analyzed. The results showed that the dimensions of student mathematical engagement that emerged during the mathematics learning process were dominated by activities comparing/classifying and justifying/reasoning. These results also have a positive impact that by using the adapted of Watson analytical tool to analyze the learning process of mathematics can help teachers to gain deeper insight into students' mathematical engagement. This technique can be used as a reference by the teacher to further analyze so that better teaching actions can be planned.